The Saloon and the Mission : Addiction, Conversion, and the Politics of Redemption in American Culture - Cannon, Eoin F., 1973- (Book collections on Project MUSE., 2013)
In this book, the author illuminates the role sobriety movements have played in placing notions of personal and societal redemption at the heart of modern American culture. The author argues against the dominant scholarly perception that recovery narratives are private and apolitical, showing that in fact the genre's conventions turn private experience to public political purpose. Further, the New Deal-era Alcoholics Anonymous refitted the "drunkard's conversion" as a model of selfhood for the liberal era, allowing for a spiritual redemption story that could accommodate a variety of identities and compulsions. The author concludes by considering how contemporary recovery narratives represent both a crisis in liberal democracy and a potential for redemptive social progress. -- Adapted from back cover.